Judith’s Embodiment as a Reversal of the Unfaithful Wife of YHWH in Ezekiel 16 - Tan, Nancy Nam Hoon (2011)
The interpretation of Judith as a literary figure of metaphorization or personification of Israel is not new. However, to focus our lenses on the embodiment of the Jewish aspirations in the figure of Judith may shed new light to interpreting this book. This article presents an interpretation of Judith’s body as a defence of the Jewish faith. At the same time, it understands such portrayals as a means of negotiating for the faithful feminine Jew in exchange for the earlier prophetic condemnation of the female bodies of unfaithful Israel/Judah, in particular Ezekiel 16. In other words, Judith becomes a means of reconstructing a new feminine identity for faithful Jews, a replacement for the metaphorical unfaithful wife of YHWH. This article shows how Judith’s body resonates the body of unfaithful Israel/Judah in four aspects: the portrayal of Judith as an embodiment of beauty, an embodiment of devout piety, an embodiment of seduction, and an embodiment of her social status.
Keywords: feminist interpretation; Ezekiel 16; Adulteress; Identity; Embodiment; Judith